K-State Turfgrass Research 2006 - Kansas State University. Agricultural Experiment Station; Cooperative Extension Service (Kansas Agricultural Experiment Station Research Reports, 2006)
Turfgrass Research 2006 contains results of projects done by K-State faculty and graduate students. Some of these results will be presented at the Kansas Turfgrass Field Day at the Rocky Ford Turfgrass Research Center in Manhattan on August 3, 2006. The enclosed articles present summaries of research projects that have been recently completed, or will be completed in the next year or two. This year's report presents summaries of research on environmental stresses, turfgrass establishment and culture, and cultivar evaluations.
Keywords: Kansas Agricultural Experiment Station contribution; no. 06-337-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 962; Turfgrass; Environmental stress; Cultivar evaluations; Bluegrass; Tall Fescue; Zoysiagrass